2009
DOI: 10.15517/rbt.v58i2.5238
|View full text |Cite
|
Sign up to set email alerts
|

Metabolitos secundarios, letalidad y actividad antimicrobiana de los extractos de tres corales y tres moluscos marinos de Sucre, Venezuela

Abstract: Secondary metabolites, lethality and antimicrobial activity of extracts from three corals and three marine mollusks from Sucre, Venezuela. The study of biochemical activity of extracts obtained from marine organisms is gaining interest as some have proved to have efficient health or industrial applications. To evaluate lethality and antimicrobial activities, some chemical tests were performed on crude extracts of the octocorals Eunicea sp., Muricea sp. and Pseudopterogorgia acerosa and the mollusks Pteria coly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
2
0
4
Order By: Relevance
“…In this study, biochemistry, molecular biology, and microbiology research areas applied to biotechnology appear strongly related since research has shown that mollusks have antimicrobial molecules as an essential line of defense to survival (He et al 2020) and important bioactive compounds that could be used in the pharmaceutical industry (Ordaz et al 2010, An et al 2019, Liu et al 2021.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, biochemistry, molecular biology, and microbiology research areas applied to biotechnology appear strongly related since research has shown that mollusks have antimicrobial molecules as an essential line of defense to survival (He et al 2020) and important bioactive compounds that could be used in the pharmaceutical industry (Ordaz et al 2010, An et al 2019, Liu et al 2021.…”
Section: Discussionmentioning
confidence: 99%
“…De igual forma los mecanismos por los cuales los componentes activos de los extractos pueden inhibir el crecimiento microbiano son los conocidos y ya mencionados: inhibición de la síntesis de la pared celular y la activación de enzimas que destruyen esa pared, aumento de la permeabilidad de la membrana celular, interferencia con la síntesis de proteínas y alteración del metabolismo de los ácidos nucleicos entre otros (Ordaz et al, 2010).…”
Section: Uso De Metabolitos Secundarios Como Antibacterianosunclassified
“…Los metabolitos secundarios son una fuente de principios activos de medicamentos y de valiosos productos químicos, cuyas aplicaciones farmacéuticas se debe a su función como analgésicos, antibacterianos, antihepatotóxicos, antioxidantes, antivirales, antitumorales, fungicidas, inmunoestimulantes, entre otras (Isaza, 2007, Pérez y Jiménez, 2011, Agustín et al, 2011 Se ha propuesto que los componentes activos de los extractos (metabolitos secundarios) pueden inhibir el crecimiento microbiano mediante los mismos mecanismos con los que actúan los antibióticos: inhibición de la síntesis de la pared celular y la activación de enzimas que destruyen esa pared, aumento de la permeabilidad de la membrana celular, interferencia con la síntesis de proteínas y alteración del metabolismo de los ácidos nucleicos entre otros (Ordaz et al, 2010).…”
Section: Introductionunclassified
“…El presente trabajo constituye una recopilación de varias investigaciones realizadas en Laboratorio de Lípidos y Productos Naturales del Departamento de Química de la Universidad de Oriente, Venezuela, en los cuales se propuso estudiar químicamente los extractos de los octocorales Eunicea sp., Muricea sp. y Pseudopterogorgia acerosa y su posible actividad biológica (Ordaz et al, 2009;Hernández et al, 2010;Ordaz et al, 2010;Camacho et al, 2014;Ordaz et al, 2014a;Ordaz et al, 2014b).…”
Section: Bioensayo Con Nauplios De Artemia Salinaunclassified